Priming recognition memory test cues: No evidence for an attributional basis of recollection. (3rd January 2020) - Ionita, Carmen F.; Talmi, Deborah; Taylor, Jason R.
Abstract: We argue that while the proposed memory model by Bastin et al. can explain familiarity-based memory judgements through the interaction of a core representation system and an attribution system, recollection-based memory judgements are not based on non-mnemonic signals being attributed to memory.